Análise empírica sobre o income shifting nas operações de empréstimos e a desatualização dos juros parâmetro - Paula, Eliane Fatima Morais de (2017)
The research aims to analyze two issues related to the transfer pricing in intercompany loans. The first purpose aims to identify evidences about the income shifting practice in the operations of loans based on EDI (Foreign Direct Investment) flows before and after the new Fiscal Law n° 12.715/2012. The current legislation has removed the benefit of safe harbor (upon Brazil Central Bank registration), requiring companies to submit their interest received or paid of loans at the transfer pricing methodology. The premise is that the release to compare the interest charged or received by intercompany, granted in previous legislation, favored the indiscriminate use of unfair rates among the business group. For the second proposal, it examines the setting of remuneration established in legal instruction and its relationship with the Emerging Markets Bond Index – Embi+, the proposal is to use this index as a proxy of remuneration to updated the yield return on date of contracting loans. The evidence of income shifting using the EDI’s flow (specific to related companies) tested by structural stability of Chow is not proven. Related to the second proposal, there is a very strong correlation between the yield return offered by public sovereigns issued in US dollars and the Embi index (years 1997 to 2016). The research also points out that outdated parameters defined by government did not affect the taxable base, if keeping beneficial to the taxpayer in borrowing, however unfavorable for loans granted